A note on double Henyey–Greenstein phase function. (November 2016) - Zhang, Feng; Li, Jiangnan
Abstract: The abnormal cases for double Henyey–Greenstein phase function are discussed. Based on an explicit analytical solution with a physical restriction, the abnormal results of double Henyey–Greenstein phase function can be removed. Abstract : Highlights: Explicit solution form for double Henry–Greenstein phase function. Removal of abnormal behavior of double Henry–Greenstein (DHG) phase function. The improved double Henry-Greenstein phase function is more accurate than HG amd DHG in general.